Validity of forensic odontology identification by comparison of conventional dental radiographs: A scoping review. Issue 1 (January 2019) - Chiam, Sher-Lin; Page, Mark; Higgins, Denice; Taylor, Jane
Highlights: There are few validation studies on using dental radiographs for forensic identification to date. An error rate could not be derived due to the heterogeneous methodologies of the reviewed studies. Further research is needed to determine an appropriate uniform framework for validation research.